2009
DOI: 10.1002/cncy.20034
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 expression in breast carcinomas

Abstract: BACKGROUND: Fine‐needle aspiration (FNA) is a rapid and accurate procedure for the detection of breast carcinomas. The evaluation of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) expression by immunohistochemistry (IHC) is performed routinely on formalin‐fixed, paraffin‐embedded needle‐core (NC) or excision tissue block (TB) preparations, according to the American Society of Clinical Oncology/College of American Pathologist guidelines. In this retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 29 publications
3
72
3
1
Order By: Relevance
“…1 Many reports specified that the same (or ''virtually'' the same) staining protocol was used for FFPE specimens as for non-FFPE cytology specimens. [5][6][7]9,10,12,14 In their survey of 28 laboratories (primarily European laboratories), Schmitt et al 18 found that IHC conditions were identical for more than 50% of laboratories for cytology specimens compared with surgical specimens, even though cell blocks were used by only 20% of laboratories. 18 Cytology IHC shares with surgical pathology the same potential sources of error in the analytic and postanalytic aspects of IHC, and there is clear evidence that major variability in IHC results can be attributed to analytic or postanalytic factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many reports specified that the same (or ''virtually'' the same) staining protocol was used for FFPE specimens as for non-FFPE cytology specimens. [5][6][7]9,10,12,14 In their survey of 28 laboratories (primarily European laboratories), Schmitt et al 18 found that IHC conditions were identical for more than 50% of laboratories for cytology specimens compared with surgical specimens, even though cell blocks were used by only 20% of laboratories. 18 Cytology IHC shares with surgical pathology the same potential sources of error in the analytic and postanalytic aspects of IHC, and there is clear evidence that major variability in IHC results can be attributed to analytic or postanalytic factors.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports of successful IHC staining on cytology specimens using a variety of preanalytic ''platforms,'' including direct smears 5 ; various monolayer preparations, such as ThinPrep (Hologic Inc, Marlborough, Massachusetts) 6,7 ; SurePath (BD Diagnostics, Franklin Lakes, New Jersey) 8 ; cytospin preparations 1,9 ; and cells removed from a stained, cover-slipped smear and transferred to another slide 10,11 ; or paraffin-embedded cell blocks prepared with or without formalin. 9,[12][13][14][15] There are no data on the number of laboratories using these different preanalytic IHC platforms in the United States.…”
mentioning
confidence: 99%
“…10% of tumor cells [16] . The scoring of HER2 was as follows [17] : Strong, circumferential membrane staining demonstrated in more than 30% of the invasive carcinoma cells was scored as 3+; moderate, circumferential membrane staining demonstrated in 10% or more of the invasive tumor cells or 3+ staining in 30% or less of the invasive tumor cells was scored as 2+ staining; weak and incomplete membrane staining presented in the invasive tumor cells was scored as 1+; and no staining shown in the tumor invasive cells was scored as 0. In the IMPC group, only the staining of the IMPC component was evaluated.…”
Section: Standardization Assessments Of the Resultsmentioning
confidence: 99%
“…However the newer techniques utilize methanol-based fixation, which interfere with immunohistochemical analysis especially for ER, PR, MIB 1 and Her 2 neu [9][10][11]. However this issue may be overcome by formalin pre-fixation prior to Cellient [7].…”
Section: Discussionmentioning
confidence: 99%